Estação Ecológica Jureia-Itatins: elementos para uma reflexão histórica - Santos, Paulo Ernani Bergamo dos (2013)
The work presented here focuses on an area of the south coast of São Paulo, the area of Jureia, which, due to its scenic beauty and its rich biological diversity, has been the scene of interests and the most diverse pressures. Since the creation of the Special Department of the Environment in 1973, which had among its assignments the decisions on deploying Ecological Stations in Brazil, this area was chosen to host one of these stations, the Ecological Station of Jureia, whose main purpose was to be the subject of scientific research in ecology - a working hypothesis that will house up here. The world demands for the conservation of nature, especially after the Stockholm Conference (1972), has made environmental degradation became a priority issue on the international agenda, which conflicted with the development policy of undeveloped countries such as Brazil. The Brazilian nuclear program, its marches and setbacks, ended up having an unexpected and critical role in the consolidation of the area as Ecological Station. It will be presented data from scientific research programs developed in the area, obtained mainly from primary sources, such as subsidies to conclude about the hypothesis